Teenagers with type 2 diabetes mellitus as a hidden population: A qualitative study of the representations and experiences related to the disease in Mazatlán, Mexico - Nathaly Llanes-Díaz; Dewi Hernández-Montoya (Journal of Health and Social Sciences)
Objective: To analyze the representations that adolescents with type 2 diabetes mellitus living in Mazatlán, Mexico have of the disease. Methods: The study design was qualitative and based on an analytical approach of narrative research. In-depth interviews and participant observation were conducted with eight adolescents (four females and four males). The sample was theoretical-intentional according to age (10-19 years), diagnosis of type 2 diabetes mellitus, and residence in Mazatlán. Results and Discussion: Adolescent experiences and representations regarding the disease were associated with six themes: 1) knowledge of the disease; 2) self-care practices; 3) identity construction; 4) significance of the disease; 5) family support; and 6) gender as a transversal category. Social stigma that is associated with diabetes and its management leading to self-management barriers, the abandonment of treatment and hiding the disease make adolescents with diabetes to be a hidden population. Identity construction is strongly affected by the disease; indeed, diabetes implied a reconstruction of male identity, while for females the disease was associated with overweight that affects their self-esteem. All of the adolescents lived in a constant dichotomy between present and future, with the fear of dying or getting worse. The absence of intergenerational communication and family support within the adolescents’ families limited adolescent care practices, exacerbating their emotional distress and living the disease with the feeling of loneliness. Conclusions: Our study showed that adolescents affected by type 2 diabetes mellitus, did not experience nor they did face the disease homogeneously but accordingly to the gender and level of family support, which, therefore, should be specifically considered by care programs and health professionals to encourage adherence to treatment, taking into account the emotional well-being and psychological needs of adolescents.